Robert Mapplethorpe: diálogos e olhares sobre a sexualidade na arte contemporânea - Silveira, Juzelia de Moraes (2009)
The present investigation developed in the Art and Visuality line of research of the Post Graduation Program in Visual Arts of the Universidade Federal de Santa Maria, RS, had the main purpose of analyzing how the contemporary artists works approaching the motto of sexuality dialogue with Robert Mapplethorpe s work, since he was one of the most significant artists to use such theme as the basis of his creative process in art. The research had as main axis the analysis of the artist s life path in which is verified in a determinant way the presence of the sexual thematic, being possible to observe the indivisibility between his personal life and his artistic work. We have tried to establish relationships between Mapplethorpe s pieces and the contemporary artists works holding the same thematic in order to observe the way how the artist s art remains current and relevant to the artistic sphere. Parallels have been established between Mapplethorpe s pieces and the selected artists ones so that we might observe several aspects of the sexuality by different glances, discussing concepts and prejudices around the theme. The main authors used were BATAILLE (1987 and 1988) FOUCAULT (1977, 1985 and 1990), PAGLIA (1993 and 1994) and CHAUÍ (1991) that approach the theme of sexuality, its repressing, and the eroticism in a comprising way; DIDI-HUBERMAN that suggests the work s spectral capacity; BARTHES (1984), FABRIS (2004, 2006), BENJAMIN (1993), LYRA and GARCIA (2002) that discuss issues about the image, and MORRISROE (1996) that presents the sexuality as decisive matter in Mapplethorpe s biography. These authors, among others, were the ones that have contributed for the research, allowing the discussion regarding the concepts analyzed. Thus, it was possible to observe that Mapplethorpe s work remains current and in constant dialogue with contemporary pieces. In these visual productions we have noticed the established sexuality, mainly by the speech created on it as well as the antagonistic forces and powers that end up for composing it.